Arabic Learning Strategy for Early Childhood in Raudhatul Athfal Harapan Bunda - Marni, Marni; Rahmi, Rahmi (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2025)
This study examines the challenges and strategies of teaching Arabic in Raudhatul Athfal Harapan Bunda, an Islamic early childhood education institution in Indonesia. Despite Arabic’s religious significance, young learners face difficulties due to its complex script, limited exposure, and reliance on traditional methods like rote memorization. Additionally, systemic barriers-such as teachers’ low Arabic proficiency (70% lack formal training), scarce interactive resources (65% of schools lack multimedia tools), and minimal parental involvement (only 40% support home practice)—hinder effective instruction. The research aims to: 1) analyze current Arabic teaching strategies, 2) evaluate their alignment with child-centered pedagogies, and 3) propose evidence-based improvements. Using a qualitative case study design, data were collected through classroom observations, teacher interviews, and document analysis. Findings reveal that multisensory methods (e.g., vocabulary songs, TPR for body parts) and interactive media (e.g., flashcards, apps) enhance engagement, corroborating theories like play-based learning, and multimedia learning. However, teacher training gaps and resource shortages limit efficacy. The study concludes by advocating for phonetics-focused teacher workshops, low-cost digital tools, and parental engagement programs to optimize Arabic acquisition.